THE SURVIVAL HANDBOOK ESSENTIAL SKILLS FOR OUTDOOR ADVENTURE - Towell, Colin
"Crammed full of preparation tips, manual skills, navigation techniques, and helpful visuals, this is your essential guide for surviving the great outdoors. Written by Colin Towell, a former SAS Combat Survival Instructor, The Survival Handbook contains all you need to get fit, gear up, and go. From survival basics such as finding water, keeping warm, and catching fish, to extreme situations including being adrift at sea, lost in the desert, or badly injured, this book will see you through the toughest times in the world's most dangerous environments. You'll discover how to read a map, navigate with or without a compass, light a fire, and make a raft or sledge. You'll learn how to build a shelter, read the weather, cross challenging terrain, treat insect and animal bites, recognise edible and poisonous plants, and cook freshly caught meat. You'll also hear inspirational real-life survival stories from fellow adventurers. What's more, you can even cook your dinner in the book's mess tin! Survival is in your hands, so don't go anywhere without this handy guide." -- Provided by publisher